Dampak Pembangunan Jalan Tol Solo-Kertosono terhadap Perubahan Sosial Pada Masyarakat Petani Desa Pisang Kecamatan Patianrowo Kabupaten Nganjuk - SAPUTRA, ASYHARI YUDHI; DIARTA, I KETUT SURYA; ASTITI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.9, No.3, Desember 2020, 2020)
The Impacts of the Solo - Kertosono Toll Road Construction on the Social Changes in the Farmers Community of Pisang Village, Patianrowo Sub-District  of Nganjuk Regency Infrastructure development, especially the Solo-Kertosono Toll Road construction has impacted on the community, especially for farmers in Pisang Village. The construction of the toll road that stretches in the agricultural area also causes the disruption of irrigation facilities. The purpose of this research is to analyze the impacts of the Solo-Kertosono toll road construction on social change, analyzed by a three-dimensional approach to social change, which includes structural, cultural, and interactional dimensions. The research location was in Pisang Village, Patianrowo Sub-District, Nganjuk Regency. Data collection used observation methods, in-depth interviews, and documentation. Determination of 10 key informants was by using purposive sampling. The method used was descriptive qualitative analysis. The results of the research on the structural dimension show that there is a change in the role of women; evidenced by the existence of several women who opened a foodstall business when building toll roads until now, but in the livelihoods and the role of farmer groups have not changed. Meanwhile, on the cultural dimension, there are problems with irrigation facilities that made farmers to use diesel pumps, while farmers' technological innovations and traditional rituals are changing but not as a result of toll road construction. On the interactional dimension, it does not change, but only changes in communication media as a result of technological progress. Suggestions that can be given are that we must evaluate and enhance the role of farmer groups as a forum for farmers and involve women in farmer group activities. The construction of new irrigation facilities needs to be done in the agricultural area located south of the Solo-Kertosono toll road.